Comparative efficacy, toxicity, and insulin-suppressive effects of simvastatin and pravastatin in fatty acid-challenged mouse insulinoma MIN6 β-cell model - Arefanian, Hossein; Sindhu, Sardar; Al-Rashed, Fatema; Alzaid, Fawaz; Al Madhoun, Ashraf; Qaddoumi, Mohammed; Bahman, Fatemah; Williams, Michayla R.; Albeloushi, Shaima; Almansour, Nourah; Ahmad, Rasheed; Al-Mulla, Fahd (Frontiers in Endocrinology, 2024)
Familial hypercholesterolemia, the highly prevalent form of dyslipidemia, is a well-known risk factor for premature heart disease and stroke worldwide. Statins, which inhibit 3-hydroxy 3-methylglutaryl coenzyme A (HMG-CoA) reductase, are the first-choice treatment for dyslipidemias, and have been effective in reducing the risk of stroke and myocardial infarction. However, emerging evidence indicates that statins may increase the incidence of new-onset type 2 diabetes by reducing β-cell mass and function. Notably, past in vitro reports studying the effects of statins on β-cells were performed without including free fatty acids in the model. This factor should have been addressed since these agents are used to treat individuals with hyperlipidemia. Here, we used a mouse insulinoma MIN6 βcell culture model to assess the efficacy, cytotoxicity, and insulin-suppressive effects of simvastatin and pravastatin in the presence of palmitic, linoleic, and oleic acids cocktail to mimic mixed lipids challenge in a biologically relevant setting. Our findings indicate that simvastatin was more effective in lowering intracellular cholesterol but was more cytotoxic as compared to pravastatin. Similarly, simvastatin exhibited a higher suppression of total insulin content and insulin secretion. Both drugs suppressed insulin secretion in phases 1 and 2, dose-dependently. No significant effect was observed on mitochondrial respiration. More importantly, elution experiments showed that insulin content diminution by simvastatin treatment was reversible, while exogenous mevalonate did not improve total insulin content. This suggests that simvastatin's influence on insulin content is independent of its specific inhibitory action on HMG-CoA reductase. In conclusion, our study identified that simvastatin was more effective in lowering intracellular cholesterol, albeit it was more toxic and suppressive of βcells function. Notably, this suppression was found to be reversible.